2019
DOI: 10.1017/s1366728919000531
|View full text |Cite
|
Sign up to set email alerts
|

Mixing the stimulus list in bilingual lexical decision turns cognate facilitation effects into mirrored inhibition effects

Abstract: To test the BIA+ and Multilink models’ accounts of how bilinguals process words with different degrees of cross-linguistic orthographic and semantic overlap, we conducted two experiments manipulating stimulus list composition. Dutch–English late bilinguals performed two English lexical decision tasks including the same set of cognates, interlingual homographs, English control words, and pseudowords. In one task, half of the pseudowords were replaced with Dutch words, requiring a ‘no’ response. This change from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 30 publications
6
40
2
2
Order By: Relevance
“…Their results were consistent with those of Poort and Rodd (2017), suggesting that stimulus list composition determines facilitation and inhibition effects during cognate recognition. Besides, Vanlangendonck et al (2020) show the unique role of identical cognates since the reaction time of non-identical cognates did not differ relative to control words in both stimulus lists. Peeters et al (2019) demonstrated that bilinguals relied on language control areas when facing cognates in a lexical decision task with a mixed-language stimulus list composition.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Their results were consistent with those of Poort and Rodd (2017), suggesting that stimulus list composition determines facilitation and inhibition effects during cognate recognition. Besides, Vanlangendonck et al (2020) show the unique role of identical cognates since the reaction time of non-identical cognates did not differ relative to control words in both stimulus lists. Peeters et al (2019) demonstrated that bilinguals relied on language control areas when facing cognates in a lexical decision task with a mixed-language stimulus list composition.…”
Section: Introductionmentioning
confidence: 86%
“…The cognate facilitation effect was mainly observed from single language stimulus list composed of cognates and matched control words from bilinguals’ first (L1) or second language (L2) only (e.g., Peeters et al, 2013 ; Xiong et al, 2020 ). Because no word belongs to any language other than the target language, any lexical activation may be regarded as evidence supporting facilitation in word recognition ( Vanlangendonck et al, 2020 ). In contrast, according to context-sensitive lexical access, the composition of the stimulus list could influence participants’ language processing ( Dijkstra and van Heuven, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One source of evidence for non-selectivity comes from studies showing cognate facilitation, in which bilinguals are faster to recognize a cognate such as "piano" in English and Spanish than a control word GRAINGER, 1998;GOLLAN;FORSTER;FROST, 1997;STEWART, 1994;COP, et al, 2017;LAURO;SCHWARTZ, 2019;ANGELE, B. et al, 2019;VANLANGENDONCK et al, 2020; BARCELOS, L.; ARÊAS DA LUZ FONTES, in press; TOASSI; MOTA; TEIXEIRA, 2020). In one of the first studies to show cognate facilitation, Caramazza and Brones (1979) had Spanish-English bilinguals perform a lexical decision task in which they had to decide if strings of letters formed a real word in their second language (L2) or not.…”
Section: Introductionmentioning
confidence: 99%